Re-evaluating Renal Angina Index: An Authentic, Evidence-Based Instrument for Acute Kidney Injury Assessment: Critical Appraisal - Raina, Rupesh; Sethi, Sidharth Kumar; Mawby, Isabelle; Datla, Nikhil; Kumar, Nikhita; Agarwal, Nirav; Tibrewal, Abhishek; Chakraborty, Ronith (Frontiers in Pediatrics, 2021)
Background/Introduction Renal angina index (RAI) used to calculate and accurately predict risk for the development of acute kidney injury (AKI) has been heavily explored. AKI is traditionally diagnosed by an increase in serum creatinine (SCr) concentration or oliguria, both of which are neither specific nor sensitive, especially among children. An RAI score may be calculated by combining objective signs of kidney dysfunction (such as SCr) and patient context, such as AKI risk factors, thus potentially serving as a more accurate indicator for AKI. Objective Due to RAI's propitious and novel nature, this editorial commentary aims to analyze the current literature on RAI and determine how well RAI serves as a predictor of AKI outcomes. Method A comprehensive literature search was conducted in PubMed/Medline and Google Scholar between January 2012 till July 2020. Literature included the prognostic aspect of early prediction of AKI in the pediatric and adult population via RAI. Results The initial literature search included 149 studies, and a total of 10 studies reporting the outcomes of interest were included. The overall sample size across these studies was 11,026. The predictive ability of RAI had a pooled (95% CI) sensitivity of 79.21%, specificity of 73.22%, and negative predictive value of 94.83%. Conclusion RAI shows benefit in the prediction of AKI among adult and pediatric populations. However, there is a lack of sufficient data and further prospective studies are needed in pediatric populations to use RAI as a principal AKI indicator among clinicians.